The Emperor of Peru - Arrabal, Fernando; Legargeant, Ken; Rooney, Mickey; Starr, Jonathan; Mercure, Monique (Cult Epics, 2010)
The parents of Toby and Liz take in a Cambodian refugee Hoang. The three bond and make the acquaintance of a crippled railroad engineer (Mickey Rooney) who lives in the woods with his own locomotive. Toby already has a very active imagination but the presence of the locomotive conjures a fantasy journey back to Cambodia to reunite Hoang with his family. An odd but occasionally endearing "family film" - families in Arrabal films are usually rife with incest, Oedipal urges, madness, delusion, matricide and patricide - "The Emperor of Peru" was a French/Canadian production little seen since its theatrical release and early eighties video release under an alternate title. It's perfectly workable as a family film but it is more of interest to Arrabal fans because of its obscurity. [www.dvdbeaver.com]
Keywords: DVD-Video